Effects of a Hydropower-Related Temporary Stream Dewatering on Fish Community Composition and Development: From Ecology to Policy - Pander, Joachim; Nagel, Christoffer; Geist, Juergen (Frontiers in Environmental Science, 2022)
Hydropower use of rivers can exert multiple effects on aquatic species and habitats. Due to limitations of conservation projects in the main channels of hydropower-affected rivers, there has been an increasing focus on tributaries, side channels, and fish passes as target areas for conservation and restoration. However, some of these side channels require frequent dewatering for their maintenance, and the ecological effects of such measures remain largely unknown. In this study, we used two dewatering events in a side channel of the River Inn as an opportunity to assess the effects of these common measures on fish. All stranded fish were collected after the two dewatering events in remaining puddles of formerly restored bank habitats, determined to species level, and measured. The fish community was compared by electrofishing before and seven weeks after the dewatering in a subset of the same habitats. The dewatering created one to three remaining puddles in the bank habitats, covering 3% of the assessed bank habitat area. In these remaining puddles, 184 stranded fish from 12 species were found, including species strictly protected under national and international law. In relation to their relative abundance, smaller and less mobile species such as Cottus gobio were mostly affected by stranding in contrast to larger and open-water-oriented species such as Chondrostoma nasus. The dewatering also caused drying out of important nursery zones, resulting in a distinctly lower recruitment success of endangered riverine fish species in the summer following the dewatering. The evidence about the negative ecological effects documented herein should be transferred into policy measures to reduce the impairment of dewatering to a minimum and to contribute to the fulfilment to national and international legal requirements. This can be achieved by reducing the extent and frequency of periodical dewatering to a minimum, by slowing down the dewatering speed, by selecting the least critical time of the year, as well as by compensation measures.